Ferromagnetic particles as magnetic resonance imaging temperature sensors - J. H. Hankiewicz (Nature Portfolio, 2016)
Magnetic resonance imaging can distinguish between different tissue types by measuring the proton distribution in a living sample. Here, the authors demonstrate how this technique can be extended to provide temperature information by using ferromagnetic particles with temperature-dependent magnetization.